Anthropological Approaches to Human-Animal Relations. The Theme of Violence - Marciniak, Katarzyna (Sensus Historiae, 2025)
The relationships between humans and animals are one of the key issues in anthropology, philosophy, and social studies. This article examines these relationships in the economic, utilitarian, and symbolic contexts, focusing on the issue of violence, particularly in the aspect of animal castration. Various approaches to analyzing these relationships are presented, ranging from Claude Lévi Strauss’ structuralism, through the reflections of Mary Douglas, to postmodern perspectives by Jacques Derrida and Donna Haraway. The phenomenon of violence against animals, including the practice of castration, is viewed as an element of human domination over other species and as an expression of beliefs about the hierarchy of “nature” and “culture.” Bruno Latour and Élisabeth de Fontenay emphasize that violence against animals, including castration, is the result of socially constructed divisions and domination. The article shows how posthumanist theory, which highlights the equality of humans and animals, raises questions about the ethical boundaries of interspecies relationships, challenging anthropocentrism and proposing a more interconnected and responsible approach to animals. Against the backdrop of theoretical considerations, contemporary changes in human-animal relations are also discussed, particularly in the context of domestic animals and their role in social life.